Atypical Pneumonia in the Elderly: A Meta-Analysis of Risk Factors, Treatment Outcomes, and Mortality - Veghasanah Tanlie; Zarfiardy Aksa Fauzi (HM Publisher, 2025)
Background: Atypical pneumonia poses a significant threat to elderly individuals, often leading to severe complications and increased mortality. This meta-analysis aimed to evaluate risk factors, treatment outcomes, and mortality associated with atypical pneumonia in elderly patients. Methods: A systematic search of PubMed, Embase, and Cochrane Library databases was conducted from January 2013 to December 2024. Studies reporting on atypical pneumonia in patients aged 65 years or older were included. Data on risk factors, treatment outcomes (clinical cure rate, radiological improvement, length of hospital stay), and mortality were extracted and pooled using random-effects models. Results: Six studies involving 1,875 elderly patients with atypical pneumonia were included. Advanced age (≥80 years), comorbidities (chronic obstructive pulmonary disease, heart failure, diabetes mellitus), and delayed initiation of antibiotic therapy were identified as significant risk factors for severe disease and mortality. Treatment with macrolides was associated with a higher clinical cure rate (OR 2.15, 95% CI 1.52-3.04, p<0.001) and shorter hospital stay (mean difference -2.8 days, 95% CI -4.1 to -1.5, p<0.001) compared to fluoroquinolones. The pooled mortality rate was 12.8% (95% CI 9.5-16.1%). Conclusion: Atypical pneumonia in the elderly is associated with significant morbidity and mortality. Early recognition of risk factors and prompt initiation of appropriate antibiotic therapy, particularly with macrolides, are crucial for improving outcomes in this vulnerable population.